Teaching science to children: - Friedl, Alfred E. (McGraw-Hill, 2005)
This comprehensive, easy-to-use text contains more than 300 science activities for the classroom. The text’s focus on the inquiry approach ties it to the inquiry-oriented National Science Education Standards for science teaching issued by the National Research Council. Each of the inquiry activities contains combined discussions of methods and content, and the text helps students overcome science anxiety by showing them how easy it is to teach science using a simple, consistent three-step approach to each of the activities (set induction, investigation, and resolution).